(untitled) (Statistics, Optimization & Information Computing, 2024)
In this article, we study and explore novel variants of Julia set patterns that are linked to the complex exponential function W(z)=pe^z^n+qz+r, and complex cosine function T(z)=(z^n)+dz+c, where n≥ 2 and c,d,p,q,rC by employing a generalized viscosity approximation type iterative method introduced by Nandal et al. (Iteration process for fixed point problems and zero of maximal monotone operators, Symmetry, 2019) to visualize these sets. We utilize a generalized viscosity approximation type iterative method to derive an escape criterion for visualizing Julia sets. This is achieved by generalizing the existing algorithms, which led to visualization of beautiful fractals as Julia sets. Additionally, we present graphical illustrations of Julia sets to demonstrate their dependence on the iteration parameters. Our study concludes with an analysis of variations in the images and the influence of parameters on the color and appearance of the fractal patterns. Finally, we observe intriguing behaviors of Julia sets with fixed input parameters and varying values of n via proposed algorithms.